Physical Activity and Ischemic Stroke Prevention - Ferfecka, Gabriela; Marta, Patrycja; Pawełek , Klaudia; Morawiecka, Natalia; Rosa-Bończak, Magdalena; Ossolińska, Agata; Huzarski, Filip; Stolarska, Lucyna; Kłosowicz, Weronika; Carlton, Olivier (Journal of Education, Health and Sport, 2025)
Introduction: Ischemic stroke is one of the most common cerebrovascular diseases, a leading cause of disability, and the primary cause of death globally. Numerous risk factors for stroke can be eliminated or mitigated through proper health-promoting measures, with regular physical activity being one of the most crucial. Exercise directly and indirectly reduces stroke risk by enhancing cardiovascular health and mitigating other risk factors. Aim of the study: This analysis is based on a review of studies and information found in the PubMed and Google Scholar databases regarding the impact of sports on the risk factors for ischemic stroke. Conclusions: The literature review indicates that sport has a direct effect on reducing the risk of ischemic stroke, but also an indirect effect in minimizing the risk factors for ischemic stroke. The existing research results have recorded a significantly beneficial impact of sport, such as the reduction of atherosclerotic changes in vessels, lowering blood pressure, and improving the elasticity of blood vessels.